Clinical impact of post procedural mitral regurgitation after transcatheter aortic valve replacement. (15th January 2020) - Ben-Assa, Eyal; Biner, Simon; Banai, Shmuel; Arbel, Yaron; Laufer-Perl, Michal; Kramarz, Judith; Elmariah, Sammy; Inglessis, Ignacio; Keren, Gad; Finkelstein, Ariel; Topilsky, Yan
Abstract: Background: While the impact of mitral regurgitation (MR) prior to transcatheter aortic valve replacement (TAVR) has been intensively studied, the implications of post-procedural MR on outcome are unknown. We investigated the clinical and physiological impact of significant MR after TAVR. Methods: Clinical and echocardiographic data of 486 patients who underwent TAVR between March 2009 and December 2014 were evaluated. Clinical endpoints included overall mortality and combined endpoint of mortality, heart failure re-hospitalization and new atrial fibrillation. Echocardiographic parameters were analyzed at baseline, 30-day and 6-month after TAVR. Results: MR severity improved in 25%, worsened in 19% and did not change in 56% of patients 30-days post TAVR (p = 0.3). Post TAVR MR grade ≥ moderate was present in 16.1%. Predictive accuracy of post TAVR MR was low (AUC = 0.63). Median follow-up was 4.3 years (interquartile range, 2.5 to 6.1). Post TAVR MR grade ≥ moderate was associated with increased mortality and combined cardiac events (p = 0.013 and p < 0.001) even when adjusted for all clinical and echo parameters and when analyzed with propensity score matching. In patients with MR ≥ moderate, LV filling pressure and RV hemodynamics worsened 6 months post TAVR, while improving in patients with less significant post procedural MR. Conclusion: Post procedural, but not pre-procedural MR grade ≥ moderate was independently associated with mortality and adverse cardiac events after TAVR. Significant MR post TAVR resulted in adverse LV and RV remodeling and poor hemodynamic. Our study strengthens the rational for initiating early treatment to reduce post TAVR MR. Highlights: Mitral regurgitation (MR) after transcatheter aortic valve replacement (TAVR) is poorly predicted by pre-procedural MR. Post TAVR, but not pre-procedural ≥ moderate MR was independently associated with mortality and adverse cardiac events. Significant MR post TAVR resulted in adverse left and right ventricular remodeling and poor hemodynamic. Our study supports initiation of early treatment to reduce post TAVR MR before ventricular dysfunction or symptoms occur.